Digital Repositories in Black Francophone African Universities - (:unkn) unknown (My University, 2016)
Francophone Black Africa consists of economically poor countries. Therefore, university budgets are almost always inadequate. Libraries and the documentation sector in general suffer from this situation. Access to scientific publications, essential to students, teachers and researchers remains a real concern despite the emergence of information and communication technologies. Indeed, scientific publications are increasingly available in the internet but are accessible at prohibitive prices. Commercial publishers have implemented strategies that allow them to control the area and draw significant revenue to the detriment of universities. Researchers and professionals of documentary and information science have denounced this situation and have proposed the creation of open archives for free and open access to scientific publications. Currently, almost all the universities in developed countries have digital repositories. The latter have several advantages among which the most important for low-income countries is free access to publications. From readings and consultation of key open archive directories, this article attempts to analyse the situation of institutional repositories in African Francophone universities. Digital sources are still on their first steps in Francophone Africa. Initiatives and open archive projects exist but they are facing restrictions and challenges that must be overcome. The pooling of resources and infrastructure appears as a necessity to achieve true digital sources.
Keywords: African Research